ISLAMIC COMMUNICATION MESSAGES FOR THE MALAY TRADITIONAL PROPOSAL EVENT OF THE DELI COMMUNITY OF NORTH SUMATRA - Qori Ananda Azhari Hasibuan; Zainun Zainun (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to explore and understand the Islamic communication messages contained in the Malay traditional engagement ceremony among the Deli community, North Sumatra. This study uses a qualitative approach with field research methods, which allows researchers to directly engage in social and cultural observations and collect data from sources involved in the tradition. The main informants in this study consisted of Shafwan Hadi Umri, Aslim, and Tengku Ismail, who each provided scientific, cultural, and practical insights regarding the traditional engagement ceremony. Secondary data were obtained through a desk study of relevant literature. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the Deli Malay traditional engagement ceremony is not only a cultural ritual, but is also rich in Islamic messages, such as polite speech, respect for parents, honesty, and silaturahmi (silaturahmi). These messages are conveyed through cultural symbols, pantun (rhymes), and figurative language, reflecting polite and wise communication in accordance with Islamic teachings. The results of this study emphasize the importance of preserving this traditional tradition so that the younger generation remains connected to a cultural identity that is rich in Islamic values.